2022
DOI: 10.1108/cms-07-2021-0309
|View full text |Cite
|
Sign up to set email alerts
|

Do corporate social responsibility reduce crash risk of stock price: evidence from China

Abstract: Purpose The 2008 global financial crisis stimulated the research interest in stock price crash risk. However, the determinants of stock price crash risk remain unclear, especially in transitional economies. The purpose of this paper is to investigate the association between corporate social responsibility (CSR) and stock price crash risk, as well as the moderating effects under different contexts. Design/methodology/approach Using firm-level data of listed firms in China from 2010 to 2019, this paper estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 92 publications
0
14
1
Order By: Relevance
“…Managers in firms with higher social responsibility may also be expected to have limited incentive to withhold bad news, thus reducing crash risk. Supporting this argument, Su and Zhou (2022) found that CSR plays an important role in constraining bad news hoarding and reducing future crash risk. Choi and Byun (2018) also provided evidence that CSR commitment leads managers to become more responsible in management, thus reducing earning management and enhancing the quality of financial information.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 93%
“…Managers in firms with higher social responsibility may also be expected to have limited incentive to withhold bad news, thus reducing crash risk. Supporting this argument, Su and Zhou (2022) found that CSR plays an important role in constraining bad news hoarding and reducing future crash risk. Choi and Byun (2018) also provided evidence that CSR commitment leads managers to become more responsible in management, thus reducing earning management and enhancing the quality of financial information.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 93%
“…‫عه‬ ‫اسس‬ ‫ععار‬ ‫أس‬ ‫عار‬ ‫انهي‬ ‫عر‬ ‫وخط‬ ‫ين‬ ‫عتثمر‬ ‫المس‬ ‫عول‬ ‫مي‬ ‫عين‬ ‫ب‬ (Alnafea & Chebbi, 2022;Cui & Zhang, 2020;Fan et al, 2021;Fu et al, 2021;Wu et al, 2021;Yin & Tian, 2017 Lee, 2016;Su & Zhou, 2023) ‫عية‬ ‫المؤسس‬ ‫عة‬ ‫الماني‬ ‫عبة‬ ‫نس‬ ‫عاات‬ ‫ي‬ ‫وع‬ ‫ب‬ (An & Zhang, 2013;Callen & Fang, 2013;Tee et al, 2018) ‫عدين‬ ‫الت‬ ‫عتو‬ ‫مس‬ ‫عاات‬ ‫ي‬ ‫وع‬ ‫ب‬ Religiosity (Callen & Fang, 2015a;Li & Cai, (Cornell et al, 2017;Firth et al, 2015;Kim et al, 2021) ‫عاع‬ ‫اافخ‬ ‫عتو‬ ‫مس‬ ‫عن‬ ‫م‬ ‫عد‬ ‫ي‬ ‫ا‬ ‫و‬ ‫عيمةب‬ ‫الس‬ ‫عار‬ ‫اسخب‬ ‫ين‬ ‫عا‬ ‫د‬ ‫عطة‬ ‫أنك‬ ‫عن‬ ‫م‬ ‫ع‬ ‫قا‬ ‫أخر‬ ‫ناحية‬ ‫ومن‬ ‫ب‬ ‫عة‬ ‫المالي‬ ‫ير‬ ‫عار‬ ‫إلالتق‬ ‫ية‬ ‫عدا‬ ‫الك‬ ‫و‬ (DeFond et al, 2015;Hutton et al, 2009;Kim & Zhang, 2014;Zhu, 2016 (Black, 1986;De Long et al, 1990;Shleifer & Vishny, 1997 (Dervishaj, 2021;Kengatharan & Kengatharan, 2014;Prosad et al, 2015) . (Black, 1986;De Long et al, 1990;Shleifer & Vishny, 1997 (Baker & Stein, 2004;Brown & Cliff, 2005;Hong & Stein, 2003 (Shefrin, 2002;Tversky & Kahneman, 1974) .…”
Section: ‫البحث‬ ‫ملخص‬mentioning
confidence: 99%
“…It has become a much more complex and impossible task to identify the impact of this information on stock markets and predict stock returns and volatility. According to Su & Zhou (2022), the global financial crisis in 2008 spurred research interest in stock price crash risk. However, the determinants of stock price crash risk still need to be clarified, especially in transition economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, the analysis suggests that sustainability efforts translate into a sustained increase in stock demand, leading to higher performance. Su & Zhou (2022) studied the relationship between CSR and stock price crash risk in the Chinese context. Based on details of listed firms in China between 2010 and 2019, they provided estimates using correlation analysis and multiple regression analysis as well as empirical proof that restricting CSR to bad news accumulation behaviour can reduce the risk of stock price crashes.…”
Section: Effects Of the Application Of Ce Principles And Capital Marketsmentioning
confidence: 99%
See 1 more Smart Citation